Effect of boost pressure on the in-cylinder tumble- motion of GDI engine under steady-state conditions using Stereoscopic-PIV - El Adawy, M. (Isfahan University of Technology, 2018)
This paper experimentally investigates the effect of boost pressure on the in-cylinder flow field under steadystate conditions using stereoscopic particle image velocimetry (Stereo-PIV) through increasing the pressure difference across the intake valves. The FEV steady-state flow bench was modified to provide an optical access into the cylinder region. The stereoscopic PIV measurements were carried out at various pressure differences viz., 300, 450, and 600 mmH2O across the intake valves of Gasoline Direct Injection (GDI) head for the mid cylinder vertical tumble-plane. Ensemble average velocity vectors were used to characterize the tumble flow structure and for the calculation of tumble ratio and average turbulent kinetic energy. Moreover, the Proper Orthogonal Decomposition (POD) technique was conducted on the PIV measured velocity vector maps to identify the most energetic structures generated at different valve lifts and pressure differences. The results of stereoscopic PIV measurements showed that the overall in-cylinder flow structures were mainly dependent on the valve lift irrespective of the applied pressure difference. However, the level of the turbulence kinetic energy increased as the boost pressure increased. Â© 2018, Isfahan University of Technology.